Cancer patients' views and understanding of genome sequencing: a qualitative study. Issue 10 (24th January 2020) - Bartley, Nicci; Best, Megan; Jacobs, Chris; Juraskova, Ilona; Newson, Ainsley J; Savard, Jacqueline; Meiser, Bettina; Ballinger, Mandy L; Thomas, David M; Biesecker, Barbara; Butow, Phyllis
Abstract : Background: Little is known about knowledge of, and attitudes towards, genome sequencing (GS) among individuals with a personal history of cancer who decide to undergo GS. This qualitative study aimed to investigate baseline knowledge and attitudes among individuals previously diagnosed with a cancer of likely genetic origin who have consented to GS. Methods: Semistructured interviews were conducted with purposively selected participants (n=20) from the longitudinal Psychosocial Issues in Genomic Oncology study, within a month of consenting to GS and prior to receiving any results. Participants were adults with a cancer of likely genetic aetiology who are undertaking GS as part of a larger genetic study. Results: Analysis identified three main themes: limited understanding of genomics; multifactorial motivation; and complex decision making. While motivations such as obtaining health information about self and family appear to be the main drivers for undertaking GS, these motivations are sometimes based on limited knowledge of the accuracy and utility of GS, creating unrealistic expectations. This in turn can prolong the deliberation process and lead to ongoing decisional conflict. Conclusion: Understanding the degree and nature of patient understanding of GS, as well as their attitudes and decision-making processes, will enable healthcare professionals to better manage patient expectations and appropriately engage and support patients to make an informed decision when pursuing GS.